Implantable wireless battery recharging system for bladder pressure chronic monitoring. Issue 22 (30th September 2015) - Young, Darrin J.; Cong, Peng; Suster, Michael A.; Damaser, Margot
Abstract : This paper presents an implantable wireless battery recharging system design for bladder pressure chronic monitoring. Abstract : This paper presents an implantable wireless battery recharging system design for bladder pressure chronic monitoring. The wireless recharging system consists of an external 15 cm-diameter 6-turn powering coil and a silicone-encapsulated implantable rectangular coil with a dimension of 7 mm × 17 mm × 2.5 mm and 18 turns, which further encloses a 3 mm-diameter and 12 mm-long rechargeable battery, two ferrite rods, an ASIC, and a tuning capacitor. For a constant recharging current of 100 μA, an RF power of 700 μW needs to be coupled into the implantable module through the tuned coils. Analyses and experiments confirm that with the two coils aligned coaxially or with a 6 cm axial offset and a tilting angle of 30°, an external power of 3.5 W or 10 W is required, respectively, at an optimal frequency of 3 MHz to cover a large implant depth of 20 cm.